ANALISIS FAKTOR YANG MEMPENGARUHI MINAT DALAM MENGEMBANGKAN TERNAK SAPI POTONG - Arif Nur Hidayat; Khairul Saleh; Faoeza Hafiz Saragih (JURNAL AGRICA, 2019)
The aim of this research is to analyze factors which affected interest in developing beef cattle. The sampling method was used Simple Random Sampling method, based on this research of the 176 population of beef cattle breeders available, 37 farmers were taken as samples. The analyze method used is multiple linear regression with dependent variable is interesting in developing beef cattle and independent variable were beef cattle seed price, education, experience and age of breeder cattle. The results show that experience effected the interest in developing beef cattle meanwhile beef cattle seed price, education and age of breeder cattle were not affected in developing beef cattle in Nagori Tempel Jaya.